2000
DOI: 10.1093/nar/28.23.4623
|View full text |Cite
|
Sign up to set email alerts
|

Divergent mechanisms of 5' 23S rRNA IVS processing in the alpha-proteobacteria

Abstract: Widespread occurrence of a separate small RNA derived from the 5'-end of 23S rRNA and of an intervening sequence (IVS) which separates this domain from the main segment of 23S rRNA in the alpha-proteobacteria implies that processing reactions which act to excise the IVS are also maintained in this group. We previously characterized the first example of processing of this IVS in Rhodopseudomonas palustris, which is classified with the Bradyrhizobia In this case, IVS excision occurs by a multistep process and RN… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
26
0

Year Published

2002
2002
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(31 citation statements)
references
References 26 publications
5
26
0
Order By: Relevance
“…It was reported that in some ␣-Proteobacteria, in addition to the RNase III cleavage in helix 9, helix 10 processing by an unknown enzyme(s) creates the 5Ј end of the 2.6-kb rRNA fragment (9,34,35). This prompted us to examine the extent of 23S rRNA sequences removed during the processing in the helix 9 region of R. leguminosarum.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…It was reported that in some ␣-Proteobacteria, in addition to the RNase III cleavage in helix 9, helix 10 processing by an unknown enzyme(s) creates the 5Ј end of the 2.6-kb rRNA fragment (9,34,35). This prompted us to examine the extent of 23S rRNA sequences removed during the processing in the helix 9 region of R. leguminosarum.…”
Section: Resultsmentioning
confidence: 99%
“…Sequencing reactions of templates with known sequences were used as a nucleotide ladder (not shown). Thus, in addition to the RNase III cleavage of the IVS in helix 9, further processing events remove the helix 10 sequences from the primary 23S rRNA transcript in R. leguminosarum, as in other ␣-Proteobacteria (34,35).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Recently, it has been reported that IVS is also present in two a -Proteobacteria members: Brucella melitensis (Bricker, 2000) and Rhizobium species (Selenska-Pobell and Evguenieva-Hackenberg, 1995). The IVS segment is removed, and further fragmentation occurs during rRNA processing (Zahn et al, 1999;Zahn et al, 2000;Zahn et al, 2001). The diversity of rRNA and rDNA described above has prompted extensive characterization and comparison.…”
Section: Introductionmentioning
confidence: 99%